Corporate social Responsibility : Linkage Business Performance and Social Performance - Balqiah, Tengku Ezni; Yuliati, Elevita; Astuti, Rifelly Dewi; Sobari, Nurdin (UI Scholars Hub, 2017)
Various types of corporate social responsibility (CSR) are perceived differently by parties associated with those activities because CSR is driven by different motives. This study investigates how CSR activities – CSR activities concerning health and well-being of mothers and children – act as liaisons between business performance (brand attitude and loyalty) and social performance (children’s quality of life). A survey was conducted in Indonesia on 450 respondents– customers of firms in industries related to natural resources and in regards to children’s well being. The data were considered via factor analysis and multiple regression analysis. The results show business, stakeholder, and moral motives. Brand attitude and loyalty can influence perceptions toward these motive. Further, these motives could increase or decrease social performance. Companies should consider the type of CSR activities to engage in because the activities can be perceived as being driven by different motives and have different impacts on social performance. This result suggests that companies can harmonize business aspects and social aspects of CSR in creating value.